Design and Dynamics Modeling of a New Two-speed Transmission - Yaogang Li; Shuo Zhang; Jue Yang; Haiyang Long; Chang Liu; Senqi Tan (Jixie chuandong)
The simple single-stage reducer used in traditional electric vehicles is not enough to meet the requirements of electric vehicle for transmission efficiency， therefore， it is necessary to introduce two or more speeds transmission to electric vehicles to improve the efficiency of the whole power assembly. A new type of electric vehicle two-speed transmission is presented， which is composed of a wedge changing mechanism and a planetary gear system， and it can realize the efficient shift without power shock. In addition， the basic structure and working principle are introduced， and Lagrange method is applied to analyze the dynamics modeling of each component of the transmission， a two-degree of freedom Lagrange equation is established， the shift process model is built based on MATLAB/Simulink， the shift process is analyzed and the accuracy of the mathematical model is verified. It provides a certain basis for the study on dynamics modeling and shift quality optimization of the same type of transmission.